The Effect of Vocabulary Mastery on Students’ Writing Skill (Research on Grade VIII Students at SMP Negeri 46 Jakarta) - Resa Siti Maesaroh; Rekno Sari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The aim of this study is to find out the Effect of Vocabulary Mastery on Students’ Writing Skill. The approach of this study is quantitative. The research is conducted at SMP Negeri 46 Jakarta, the total sample of this research followed by 20 students of grade VIII at SMP Negeri 46 Jakarta. The sampling technique is probability random sampling. The techniques of collecting data used are test to get the vocabulary mastery score and writing skill to know of students’ writing skill of description text. The techniques of analyzing data used simple linear regression and significant test. The result of analysis shows that there is positive effect students’ vocabulary mastery on students’ writing skill of grade VIII at SMP Negeri 46 Jakarta. This is obtained from the data, the value of Fcount > Ftable is a value of Fcount 5,67 ≥ Fcount 4.74, which show Fcount > Ftable.Keywords: Vocabulary Mastery, Students’ Writing Skill